Risk factors for major adverse cardiovascular events after the first acute coronary syndrome. (1st January 2021) - Okkonen, Marjo; Havulinna, Aki S.; Ukkola, Olavi; Huikuri, Heikki; Pietilä, Arto; Koukkunen, Heli; Lehto, Seppo; Mustonen, Juha; Ketonen, Matti; Airaksinen, Juhani; Kesäniemi, Y. Antero; Salomaa, Veikko
Abstract: Aims: To evaluate risk factors for major adverse cardiac event (MACE) after the first acute coronary syndrome (ACS) and to examine the prevalence of risk factors in post-ACS patients. Methods: We used Finnish population-based myocardial infarction register, FINAMI, data from years 1993–2011 to identify survivors of first ACS ( n  = 12686), who were then followed up for recurrent events and all-cause mortality for three years. Finnish FINRISK risk factor surveys were used to determine the prevalence of risk factors (smoking, hyperlipidaemia, diabetes and blood pressure) in post-ACS patients ( n  = 199). Results: Of the first ACS survivors, 48.4% had MACE within three years of their primary event, 17.0% were fatal. Diabetes (p = 4.4 × 10 −7 ), heart failure (HF) during the first ACS attack hospitalization (p = 6.8 × 10 −15 ), higher Charlson index (p = 1.56 × 10 −19 ) and older age ( p  = .026) were associated with elevated risk for MACE in the three-year follow-up, and revascularization ( p  = .0036) was associated with reduced risk. Risk factor analyses showed that 23% of ACS survivors continued smoking and cholesterol levels were still high (>5mmol/l) in 24% although 86% of the patients were taking lipid lowering medication. Conclusion: Diabetes, higher Charlson index and HF are the most important risk factors of MACE after the first ACS. Cardiovascular risk factor levels were still high among survivors of first ACS.